Penerapan tutor sebaya menggunakan metode diskusi untuk meningkatkan hasil belajar matematika siswa kelas V SDN 02 Mesoyi - Wawan Junari (Action Research Journal, 2021)
The purpose of this study was to determine whether the application of the peer tutor learning model using the discussion method could improve student learning outcomes. This research is a classroom action research that is applied to the fifth grade students of SDN 02 Mesoyi as many as 20 students. This research was designed in two cycles, each cycle carried out in the stages of planning, implementation, observation, and reflection. The results of this study indicate that peer tutoring learning using the discussion method with LKS media can improve students' cognitive abilities in solving problems, teacher performance is able to carry out learning with peer tutor learning models using discussion methods with LKS media well. Suggestions in this study is that teachers should use peer tutor learning models using discussion methods with LKS media can be used as an alternative to improve student learning outcomes.